Institutional factors enhancing and affecting service delivery in Lekwa Local Municipality - Tsotetsi, Biotumelo (University of the Witwatersrand, Johannesburg, 2024)
The discourse surrounding South African local governments often highlights deficiencies in the efficient and effective delivery of basic social services. This study was motivated by the absence of viable solutions to the persistent challenges facing service delivery in local municipalities, and the Lekwa Local Municipality was no exception. Situated in the Mpumalanga Province, the Lekwa Local Municipality serves as a compelling case study to explore the institutional challenges that both enhance and hinder service delivery. The municipality has grappled with significant administrative instability and a lack of political oversight. Consequently, its capacity to deliver services has been severely compromised. These institutional challenges have manifested in various forms, including bureaucratic inefficiencies, inadequate resource allocation, and a lack of strategic planning and implementation. As a result, the municipality has struggled to meet the needs of its residents and address pressing socio-economic issues within its jurisdiction. By examining the institutional factors contributing to these challenges, this study seeks to provide valuable insights into the complexities of service delivery in local government settings. By understanding the root causes of these issues, policymakers, stakeholders, and community members can work towards implementing targeted interventions to improve governance processes, enhance accountability mechanisms, and ultimately, strengthen the capacity of local municipalities to deliver essential services to their constituents. The Lekwa Local Municipality has witnessed unrest and protest, due to poor service delivery. The research employed a qualitative approach, utilizing a non-probability purposive sampling technique to select fourteen participants. This method was chosen deliberately to ensure that participants possessed relevant insights and experiences related to the research topic. Data collection was conducted through face-to-face semi-structured interviews, allowing for in- depth exploration of participants' perspectives, experiences, and opinions. The study's findings shed light on persistent challenges within the Lekwa Local Municipality despite the introduction of new leadership initiatives aimed at enhancing service delivery. A critical issue identified is the dire lack of leadership at both the political and administrative levels, resulting in a vacuum of oversight and accountability. This lack of effective leadership v has allowed self-interest and expediency to prevail, undermining the municipality's ability to fulfil its mandate. The study concludes by stating findings underscore the urgent need for comprehensive reforms within the Lekwa Local Municipality to address the root causes of poor service delivery. This includes strengthening leadership and accountability mechanisms, implementing transparent and accountable governance practices, and mobilizing resources effectively to ensure the delivery of quality services to residents. Only through concerted efforts to address these challenges can the municipality begin to regain the trust and confidence of its constituents and achieve meaningful improvements in service delivery outcomes.
A research report submitted in fulfillment of the requirements for the Master of Management in Governance (Public Policy), In the Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; SERVICE DELIVERY; LEKWA LOCAL MUNICIPALITY; INSTITUTIONAL FACTORS; SDG-16: Peace, justice and strong institutions; SDG-11: Sustainable cities and communities